Slang in â€œIf You Know What Happened in MCIâ€ - Intan Riany Mandala (RETORIKA: Jurnal Ilmu Bahasa, 2018)
Abstractâ€”This study classifies the form and formation of slang as a kind of an extra-linguistic form. To achieve the objective, the theory of word formation (Ridwan, 2003) was used. Data were obtained from â€œIf You Know What Happened in MCIâ€ novel. Referential method was made use in analyzing the data. The results of data analysis show that slang language occurs not only at the word level, but also at phrase and clause level. The majority, however, occurs at the word level. Language types included in the slang construction are not bound to one language but of many kinds, such as Indonesian, English, local language, mixture of two different languages and some of unrecognizable languages which were intensely code-mixed. Slang are formed through ten processes: coinage; borrowing; compounding; blending; clipping; conversion; back formation; acronym; derivation; multiple processes. Future nature of language would be adding on the existing theory of word formation, particularly that of morphological process of new words formation. Keywords: Slang; word formation; â€œIf You Know What Happened in MCIâ€ novel